Cave-scale 3D finite-discrete element method modelling - Xu, Y.-H.; Li, Y.; Jakubec, J.; Thomas, A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The reliable prediction of caveability, cave breakthrough and subsequent subsidence is critical for cave mining. While continuum-based numerical methods are computationally efficient for large-scale analysis, they are often limited in their ability to explicitly simulate the complex kinematic and fracturing mechanisms associated with cave propagation, large-scale displacement, and the transition from relatively intact rock to a mobilised caved mass. This paper presents a 3D finite discrete element method (FDEM) approach to simulate the complete caving process, from initiation and propagation to surface breakthrough and crater formation. By integrating fracture mechanics principles, the proposed 3D FDEM framework explicitly models the progressive degradation of the rock mass from a continuum to a discontinuum state through stressinduced fracturing and the mobilisation of discrete blocks. The model incorporates a discrete fracture network (DFN) to represent the inherent structural heterogeneity of the rock mass, allowing for the simulation of realistic failure mechanisms. The results highlight that explicit consideration of brittle fracture processes and structural kinematics is essential for reliable forward analysis of the caving process.